Parameter genetik padi beras merah (Oryza sativa L.) yang ditanam pada lahan kering dengan sistem gogo - Kamalia Safitri, Devi; Aryana, I Gusti Putu Muliarta; Sudika, I Wayan (Universitas Muhammadiyah Mataram, 2024)
Crossing of F2BC4P19-36 promising line with IPB 3S variety resulted in red rice strains. These strains were selected until obtaining the F5 generation. The research aimed to determine the genetic diversity, heritability values, and genotypic correlation coefficients among quantitative traits for yield of red rice strains in dryland with a continuous cropping system. The study was conducted from May to September 2023 in Tampak Siring Village, Batukliang, Central Lombok Regency, West Nusa Tenggara. It employed a Randomized Complete Block Design (RCBD) with 14 genotypes, replicated three times, totaling 42 treatments. Data analysis was performed using Analysis of Variance (ANOVA) at a 5% significance level. Genetic diversity, assessed broadly, was indicated by traits such as the number of unproductive tillers, number of filled grains, and number of unfilled grains; moderately by traits such as number of productive tillers, total tillers, 100-grain weight, and grain weight per panicle; and narrowly by traits such as plant height, panicle length, flowering duration, and harvesting period. Heritability values were high for yield, moderate for total tillers, number of filled and unfilled grains, 100-grain weight, and flowering duration, and low for traits like plant height, number of productive and unproductive tillers, panicle length, grain weight per panicle, and harvesting period. Genotypic correlation coefficients showed positive associations with yield for traits such as panicle length, grain weight per panicle, and flowering duration, whereas negative correlations were observed with yield for the number of unproductive tillers. Genetic diversity, heritability values, and correlation coefficients serve as determinants for selection criteria